Una nueva especie de Capuchino (Sporophila: thraupidae) de los Esteros del Iberá, Corrientes, Argentina - Di Giacomo, Adrián Santiago; Kopuchian, Cecilia (Nuestras Aves, 2016)
Este artículo no cuenta con un resumen.